1999
DOI: 10.1093/cercor/9.8.896
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in the Inferior Parietal Lobule

Abstract: The inferior parietal lobule (IPL) - a neocortical region and part of the heteromodal association cortex (HASC) - has been hypothesized to exhibit sexual dimorphism, as do other HASC regions, particularly with regard to asymmetry. Using a reliable method for measuring IPL gray matter volume based upon individual sulcal-gyral landmarks, we measured this region on magnetic resonance imaging scans from a sample of 15 individually matched pairs of normal male and female subjects. Male subjects showed significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
45
1
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(56 citation statements)
references
References 59 publications
8
45
1
2
Order By: Relevance
“…This result is in agreement with the neuroimaging data of Frederikse et al 36 that the volume of the IPL in males is normally asymmetric (L>R), and this asymmetry is decreased in schizophrenia 3,36 . A functional MRI study 37 also demonstrated that the largest functional asymmetries (L>R) are in the IPL in healthy controls but not in schizophrenia patients during the resting state.…”
Section: Oligodendrocyte Density and Asymmetrysupporting
confidence: 93%
“…This result is in agreement with the neuroimaging data of Frederikse et al 36 that the volume of the IPL in males is normally asymmetric (L>R), and this asymmetry is decreased in schizophrenia 3,36 . A functional MRI study 37 also demonstrated that the largest functional asymmetries (L>R) are in the IPL in healthy controls but not in schizophrenia patients during the resting state.…”
Section: Oligodendrocyte Density and Asymmetrysupporting
confidence: 93%
“…Sex-related differences in this region had been previously found, but with inconsistencies between studies using VBM and manual segmentation. 14,16,44 Our findings regarding patients with AS substantiate the view that atypical expression of sex differences is linked to the etiology of AS. Because the key findings were interactions between sex and diagnosis, this indicates that investigating atypical sexual dimorphism in AS is essential to gain insight into the etiology of the condition.…”
Section: Discussionsupporting
confidence: 81%
“…Compared to placebo, the ERT-treated group in that study showed increased activation of the inferior parietal lobule during storage of nonsense words. That same brain region shows activation associated with the storage and retrieval of phonological material during a working memory task [24] and structural sex differences in regional brain volume [11]. Together, these studies suggest several mechanisms by which estrogen may enhance verbal memory.…”
Section: Introductionmentioning
confidence: 77%